Novel sol-gel hybrid methltrimethoxysilane-tetramethoxysilane sorbent cartridge for solid phase extraction of organophosphorus pesticides - Wan Ibrahim, Wan Aini (2011)
A novel sol-gel hybrid methyltrimethoxysilane-tetraethoxysilane (MTMOS-TEOS) was produced and applied as sorbent for solid phase extraction (SPE). Five selected organophosphorus pesticides (OPPs) were employed as model compounds to evaluate the extraction performance of the synthesized sol-gel organic-inorganic hybrid MTMOS-TEOS. Analysis was performed using gas chromatography-mass spectrometry. Several important SPE parameters were optimized. Under the optimum extraction conditions, the method using the sol-gel organic-inorganic hybrid MTMOS-TEOS as SPE sorbent showed good linearity in the range of 0.001-1 μg L(-1), good repeatability (RSD 2.1-3.1%, n=5), low limits of detection at S/N=3 (0.5-0.9 pg mL(-1)) and limit of quantification (1-3 pg mL(-1), S/N=10). The performance of the MTMOS-TEOS SPE was compared to commercial C18 Supelclean SPE since C18 SPE is widely used for OPPs. The MTMOS-TEOS SPE method LOD was 500-600 × lower than the LOD of commercial C18 SPE. The LOD achieved with the sol-gel organic-inorganic hybrid MTMOS-TEOS SPE sorbent allowed the detection of these OPPs in drinking water well below the level set by European Union (EU) at 0.1 μg L(-1) of each pesticides. The developed MTMOS-TEOS SPE method was successfully applied to real sample analysis of the selected OPPs from several water samples and its application extended to the analysis of several fruits samples. Excellent recoveries and RSDs of the OPPs were obtained from the various water samples (recoveries: 97-111%, RSDs 0.4-2.8%, n=3) and fruit samples (recoveries: 96-111%), RSDs 1-4%, n=5) using the sol-gel organic-inorganic hybrid MTMOS-TEOS SPE sorbent. Recoveries and RSDs of OPPs from river water samples and fruit samples using C18 Supelclean SPE sorbent were 91-97%, RSD 0.9-2.6, n=3 and 86-96%, RSD 3-8%, n=5, respectively). The novel sol-gel hybrid MTMOS-TEOS SPE sorbent demonstrate the potential as an alternative inexpensive extraction sorbent for OPPs with higher sensitivity for the OPPs.